The clinical management and efficacy of metagenomic next-generation sequencing in patients with pyogenic spinal infection: a single-center cohort study - Maoyang Qi; Yueqi Du; Jian Guan; Jiao Ma; Wenwen Li; Zan Chen; Wanru Duan (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aims to evaluate the clinical management and effectiveness of metagenomic next-generation sequencing (mNGS) in patients with pyogenic spinal infections. Methods We conducted a retrospective review of 17 patients diagnosed with pyogenic spinal infections and treated at our institution between October 2022 and February 2024. The cohort included 8 males and 9 females, with a mean age of 63.59 ± 10.18 years (range: 41–71 years). The infections comprised 9 epidural abscesses, 6 intervertebral space infections, and 2 deep abscesses. All patients underwent open surgical procedures and mNGS-based bacterial identification using intraoperative pus or tissue specimens, in addition to conventional blood bacterial cultures. Clinical outcomes were assessed using CRP, PCT, WBC inflammatory markers, and VAS scores postoperatively. Results All 17 patients with pyogenic spinal infections underwent open surgery and mNGS bacterial detection at our institution. Among the 17 patients, mNGS yielded positive results in 14 cases (82.4%), significantly higher than the 5.9% positivity rate of conventional bacterial cultures (p < 0.001). The mNGS test time was notably shorter than conventional cultures (1.0 vs. 5.88 days, p < 0.001). Postoperative antibiotic therapy was adjusted based on mNGS findings. There were significant reductions in postoperative VAS, WBC, PCT, and CRP values compared to preoperative levels (p < 0.01). Conclusion Metagenomic next-generation sequencing is effective in managing pyogenic spinal infections by facilitating rapid and sensitive detection of pathogens. This technique improves the timeliness and accuracy of diagnosis, highlighting its potential for broader clinical use.